Fine forecasts: encouraging the media to include ultraviolet radiation information in summertime weather forecasts - Richards, R; Reeder, A I; Bulliard, J-L (Health education research, 2004)
Melanoma and skin cancer are largely attributable to over-exposure to solar ultraviolet radiation (UVR). Reports of UVR levels within media weather forecasts appear to be well received by the public and have good potential to communicate the need for appropriate sun protection to a broad audience. This study describes provision of UVR messages by New Zealand newspapers, radio and TV stations over a 4-year period, and examines the impact of an intervention which aimed to address media concerns about the financial costs of accessing UVR information for broadcast. Newspaper and radio presentation of UVR information increased immediately after these costs were removed; however, among radio stations it dropped in subsequent years. Among those media that were presenting UVR, this information was broadcast throughout the summer period and repeated throughout the day. Furthermore, most reports included concomitant, behavioral sun protection messages. At the final assessment (summer 2001/02), 66% of radio stations, both TV channels and 48% of newspapers reported UVR information in summertime weather reports. Efforts to further increase UVR presentation will need to address media concerns about time constraints on weather forecasts and media perceptions of poor audience demand or understanding of some UVR messages.